Bài 3: Rút gọn phân thức

Nguyễn thị lan

\(Với\) x khác 1,-1.tính Q=\(\frac{x+3}{x+1}-\frac{2x-1}{x-1}-\frac{x-3}{x^2-1}\)

Online Math
3 tháng 3 2020 lúc 21:20

Làm

Với x khác 1, -1 ta có:

Q=\(\frac{x+3}{x+1}-\frac{2x-1}{x-1}-\frac{x-3}{\left(x-1\right)\left(x+1\right)}\)

Q=\(\frac{\left(x+3\right)\left(x-1\right)}{\left(x-1\right)\left(x+1\right)}-\frac{\left(2x-1\right)\left(x+1\right)}{\left(x-1\right)\left(x+1\right)}-\frac{x-3}{\left(x-1\right)\left(x+1\right)}\)

Q=\(\frac{x^2+2x-3-2x^2-x+1-x+3}{\left(x-1\right)\left(x+1\right)}\)

Q=\(\frac{-x^2+1}{\left(x-1\right)\left(x+1\right)}\)

Q=\(\frac{\left(1-x\right)\left(1+x\right)}{\left(x-1\right)\left(x+1\right)}=-1\)

Vậy......

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN